2001
DOI: 10.1128/jvi.75.15.6941-6952.2001
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regulation of Human Immunodeficiency Virus-Infected CD4+Lymphocytes by a Synthetic Immunomodulator Leads to Potent Virus Suppression In Vitro and in hu-PBL-SCID Mice

Abstract: We have previously observed that the synthetic immunomodulator Murabutide inhibits human immunodeficiency virus type 1 (HIV-1) replication at multiple levels in macrophages and dendritic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 72 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, the role of Oct-1 in HIV-1 transcription has also been indirectly highlighted by Bahr and co-workers. They have demonstrated that murabutide, which is a clinically acceptable immunomodulator presenting the capacity to decrease HIV-1 transcription (43,44), presents the ability to induce Oct-1 expression and DNA-binding activity in HIV-1 infected macrophages (45). These results suggest that the murabutide-induced suppression of HIV-1 transcription could be mediated, at least in part, by its capacity to increase Oct-1 expression (45).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the role of Oct-1 in HIV-1 transcription has also been indirectly highlighted by Bahr and co-workers. They have demonstrated that murabutide, which is a clinically acceptable immunomodulator presenting the capacity to decrease HIV-1 transcription (43,44), presents the ability to induce Oct-1 expression and DNA-binding activity in HIV-1 infected macrophages (45). These results suggest that the murabutide-induced suppression of HIV-1 transcription could be mediated, at least in part, by its capacity to increase Oct-1 expression (45).…”
Section: Discussionmentioning
confidence: 99%
“…Romurtide and B30‐MDP 8 were found to limit infection by herpes simplex virus type 1, herpes simplex virus type 2 and vaccinia virus . Moreover, murabutide 10 has been shown to limit HIV‐1 viral loads in a humanised murine model . However, it remains uncertain whether these effects are truly via long‐term epigenetic reprogramming as many of the assays were conducted soon after adjuvant administration.…”
Section: Peptidoglycan Metabolites and Adjuvanticitymentioning
confidence: 99%
“…105 Moreover, murabutide 10 has been shown to limit HIV-1 viral loads in a humanised murine model. 106 However, it remains uncertain whether these effects are truly via long-term epigenetic reprogramming as many of the assays were conducted soon after adjuvant administration.…”
Section: Peptidoglycan Metabolites and Adjuvanticitymentioning
confidence: 99%
“…Additional support for the capacity of MB to regulate the expression of cellular genes, and consequently to inhibit viral replication, has been provided by a recent study using endogeneously infected lymphocytes. Thus, MB‐treated CD4 + cells from HIV‐infected patients were found to down‐regulate the expression of c‐myc, a host factor known to be essential for the nuclear transport of preintegration complexes in activated T‐lymphocytes [20].…”
Section: Introductionmentioning
confidence: 96%